Comparative Study of Hypertension Prevalence, Health‐Related Quality of Life, and Healthcare Barriers Among Diabetic and Non‐Diabetic Populations in Urban Slums of Bangladesh: A Community‐Based Comparative Cross‐Sectional Study - Md. Fakhrul Islam Maruf; Nishat Tamanna Omi; Mahfuza Mubarak (Health Science Reports, 2026)
ABSTRACT Background and Aims The double burden of diabetes and hypertension is a growing public health concern in Bangladesh's urban slums, where healthcare access and health‐related quality of life (HRQoL) remain limited. This study compared hypertension prevalence, HRQoL, and healthcare barriers between adults with and without self‐reported diabetes, and identified factors independently associated with hypertension and HRQoL in this population. Methods A community‐based comparative cross‐sectional study was conducted from June to August 2025 in five purposively selected urban slums of Dhaka. Using simple random sampling, 400 adults aged ≥ 45 years (200 with self‐reported diabetes, 200 without) were recruited. Data were collected using the validated Bengali WHO STEPS questionnaire and the EQ‐5D‐5L instrument. Multivariable logistic regression identified factors independently associated with self‐reported hypertension (the primary, prespecified outcome), with diabetes status entered as the key exposure variable, and multivariable linear regression examined factors associated with the EQ‐5D‐5L index score. Results Hypertension was more prevalent among participants with diabetes (121/200, 60.5%) than without (46/200, 23.0%; χ 2 = 57.8, p < 0.001). After adjustment, diabetes remained the strongest independent correlate of hypertension (adjusted odds ratio [aOR] 3.82, 95% CI 2.46–5.93, p < 0.001), alongside older age, higher body mass index, smoking, and non‐manual occupation. Diabetic participants had significantly lower EQ‐5D‐5L index scores (0.72 ± 0.18 vs. 0.85 ± 0.12, p < 0.001); this association persisted after adjustment ( β = −0.081, 95% CI − 0.104 to −0.058, p < 0.001). Among participants with diabetes, financial constraints were the leading healthcare barrier (167/200, 83.5%). Conclusion Diabetes is strongly and independently associated with hypertension and impaired HRQoL among older adults in Dhaka's urban slums. Financial constraints dominate healthcare access barriers. Equity‐focused, integrated NCD interventions targeting this vulnerable population are urgently needed.